2021
DOI: 10.1007/s00784-021-03841-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in clinical parameters following adjunctive local sodium hypochlorite gel in minimally invasive nonsurgical therapy (MINST) of periodontal pockets: a 6-month randomized controlled clinical trial

Abstract: Background The mechanical disruption and removal of the subgingival biofilm represent the most important step in the treatment of periodontitis. However, in deep periodontal pockets, mechanical removal of the subgingival biofilm is difficult and frequently incomplete. Preliminary findings indicate that the use of amino acid buffered sodium hypochlorite (NaOCl) gel may chemically destroy the bacterial biofilm and facilitate its mechanical removal. Objectives … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 31 publications
0
32
0
1
Order By: Relevance
“…Nevertheless, its use was associated with significantly reduced recolonization of the sites by T. denticola and T. forsythia [ 22 ]. By contrast, the adjunctive benefit of sodium hypochlorite gel formulation for minimally invasive non-surgical therapy (MINST) was positively evaluated by a recent RCT [ 15 ]. The authors compared the outcome of step-2 therapy after delivering it to untreated stage-3 and -4 periodontitis patients in both study arms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, its use was associated with significantly reduced recolonization of the sites by T. denticola and T. forsythia [ 22 ]. By contrast, the adjunctive benefit of sodium hypochlorite gel formulation for minimally invasive non-surgical therapy (MINST) was positively evaluated by a recent RCT [ 15 ]. The authors compared the outcome of step-2 therapy after delivering it to untreated stage-3 and -4 periodontitis patients in both study arms.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, a novel amino-acid-buffered sodium hypochlorite cleaning gel exhibiting antimicrobial potential was significantly effective in improving the outcome of non-surgical therapy and, thus, significantly reduced counts of Gram-negative pathogens in an artificial biofilm model [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that the formation of miRNA-584 is induced by P. gingivalis lipolysaccharides (LPS). This miRNA, produced by bacterial induction, causes upregulation of IL-8 within gingival epithelial cells by inducing the repression of the lactoferrin receptor, which, if not inhibited, would induce an antimicrobial effect [ 13 , 27 , 28 ].…”
Section: Mirna Molecular Signalling and Periodontal Diseasementioning
confidence: 99%
“…is is due to the transmission of the Streptococcus mutans being significantly augmented when inappropriate behaviors [24][25][26] are pursued such as the usage of the baby bottle, the pacifier, or the same cutlery not clean shared with the parent's saliva [3,[27][28][29][30][31][32]. In this respect, the mother can be an important font of transmission in children especially in the first two years of life, when Streptococci mutans are initially transferred, especially using dental materials [3,[33][34][35][36]. us, if the mother does not follow appropriate behaviour of oral hygiene [27][28][29][30][31], the risk of development of cavities in the child increases since the concentration of bacteria is higher and more aggressive [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%